Strategic cultivar and sowing time selection for weed management and higher redgram productivity in semi-arid Indian regions - Marimuthu, S.; Byrareddy, Vivekananda M.; Dhanalakshmi, A.; Mushtaq, Shahbaz; Surendran, U. (Frontiers in Environmental Science, 2024)
Redgram (Cajanus cajan L. Mill sp.), a leguminous crop commonly grown in tropical and subtropical climates, is highly valued for its high protein content (21%), which contributes significantly to food and nutritional security. However, its production faces challenges primarily due to terminal dryness experienced during critical growth stages because of changing rainfall patterns. To overcome this, adaptive techniques become imperative as the productivity of this crop is intricately linked to environmental factors and the crop's growth cycle. Hence, the field experiment was conducted at the National Pulses Research Centre, Vamban, Pudukkottai, Tamil Nadu, in South India under rainfed condition, during the kharif (monsoon) seasons of 2017-18 and 2018-19. The primary objectives were to determine the optimal sowing time and identify suitable redgram cultivars, especially in the context of the late onset of the monsoon in Tamil Nadu, a common issue under changing climate conditions.The experiments tested six different sowing dates with three redgram cultivars, the findings highlighted the substantial influence of different redgram cultivars and sowing times on the crop's growth characteristics and yield. Among the six sowing dates tested, planting in later half of June (S6) resulted in notably higher plant height (201 cm), a greater number of pods per plant (287), a seed yield of 1112 kg ha -1 , and a benefit-cost ratio of 2.61 Notably, this sowing period (S6) demonstrated comparable performance with the treatment of redgram sowing in the latter part of September (S4). CO 6 (V1) is the most productive of the three redgram cultivars, with the highest mean pant height (200 cm), number of pods per plant (237), grain yield (1017 kg ha -1 ), and benefit cost ratio (2.38). Extended phenological phases along with extra days to reach phenological stages could account for the increased yield in comparison to the other cultivars. Among the two short-duration cultivars, VBN (Rg) 3 (V3) had a significantly higher mean grain yield of 958 kg ha -1 with the benefit-cost ratio of 2.24. Consequently, the shortduration redgram cultivars emerge as highly suitable choices for integrating into crop sequences, thereby augmenting farm cropping intensity.